Archipelagic Futures: The Speculative and Decolonial Transecopoetics of Roque Raquel Salas Rivera - Ysabel Muñoz-Martínez (eTropic: electronic journal of studies in the tropics)
Puerto Rico’s experience of Hurricane Maria became an inflection point for the island’s inhabitants, diaspora, literary and artistic communities, uncovering and stressing the overlapping crises that continue ailing the country. This paper discusses how political ecology and gender non-normativity are fundamental axes to approach Puerto Rican poet Roque Raquel Salas Rivera’s decolonial proposal of futurity in the face of overlapping disasters. It directly engages with poems from the collection antes que isla es volcán/ before island is volcano (2022), explaining the operations through which his poetry speculates and performs gender, social, political, and environmental justice. Utilizing frameworks from transecology and Caribbean chronotropics, I identify three main operations contributing to forging decolonial futures: the development of affective eco-literacies to approach the future, breakage of normative time, and geological trans-speciation as a key rhetorical figure. These poetic engage-ments allow Salas Rivera to reimagine a nation outside the plantation logic that attempts to tie the Caribbean to endless regimes of extraction. Instead, the poet designs a chronotropics pointing towards novel forms of futuring in the tropics and beyond.